Technology venture blueprint by Quickey Sdn. Bhd. / Nur Nabila Mazlan...[et al.] - Mazlan, Nur Nabila; Hamid, Wan Nadzirah; Mohd Sakri @ Shukri, Muhammad Taariq; Abdullah, Nurbaizura Lawyiai; Kuip, Bowie (2017)
Keys are one of the essential things to bring before going out from the house. Carrying so many keys that are usually used in daily lives can be a real problem with them often being misplaced, bulky to be keep in the pocket, always gone missing in handbag and can be annoying they constantly jiggles while walking. Pro-Key by Quickey Sdn. Bhd. is a key organizer that was designed as an answer for bulky, annoying and missing keys. Pro-Key is sleek, lightweight, portable and comes with Bluetooth to track down your keys. Quickey Sdn. Bhd. is a new company based in Malaysia that provides premium pocket key organizers, Pro-Key, which are compact yet functional in holding up to 10 keys and incredibly versatile with a wide selection of accessories. Pro-Key comes with a tracker technology that alerts you within the Bluetooth range via phone app. If you lost Pro-Key, the app will track the current location of your Pro-Key and it also comes with custom separation alerts that notifies you when you are about to leave Pro-Key behind. The target market of our product is to provide custom key organizer for all levels of customers either individuals, in a households or even for universities students in all genders that have problems to hold or carry bunch of their keys and lost them frequently. Our major target market size is mostly from working individuals and households while there might be some small potential buyers among the universities students in considering their financial income. In fact, we are expecting the growth of our product will be increased in marketing by build a cooperation with knowledgeable sales people. Furthermore, in manufacturing, we plan to hire cheap labour and train them to customize the production of pro-key, and purchase wholesale components in bulk to cut down on costs. As for the business, we are providing a key organizer which can fit up to 10 keys and other useful accessories such as a tracking device with the latest version of wireless technology Bluetooth 4.0 with range approximately above 300 meters, a 32GB thumb drive, bottle opener, torchlight, and a pocket knife. Besides, it is highly audible alert which increases the chances of finding lost keys even when completely out of range.